(untitled) (Journal of Tikapur Multiple Campus, 2018)
Marriage rateuli in Achham is remarkable for its typical performance of deuda dance and songs of mixed emotions among women in the night time of marriage day at bridegroom’s home. Among its four stages of performing deuda dance, the stage of deuda khel and real rateuli embody the real and traditional convention of rateuli performance with a humorous performance of a typical female character called dyangsya than the stages, dio mano and balokhelaune. But today, the traditional convention of performing marriage rateuli has been dynamic and modified with an easy inclusion of male and female performers due to the influence of other culture, technology, commercialization and visualization of deuda dance and song and growing women education. This article attempts to present a comparative study of marriage rateuli in Achham from the contour of its performativity and its gender dynamism with their brief analytical information.